KINETIC STUDY OF THE DECOMPOSITION OF AMMONIUM PERCHLORATE - PRIANTO (NIM : 20910009); Pembimbing : Dr. Muhamad Abdulkadir Martoprawiro, BAYU
The kinetics prestudy of decomposition of ammonium perchlorate to oxygen at various temperature (298.15 K, 473.15 K, 673.15 K, 873.15 K and 1073.15 K) has performed in this research. The basis sets B3LYP/6-311+G(3df,2p) is used in the calculation of the decomposition of ammonium perchlorate reactions. The calculations of rate constant reaction were performed in all reactions of decomposition step of ammonium perchlorate, using Arhennius theory and collision theory calculation. The new pathways for the decomposition steps of ammonium perchlorate to oxygen have been found, that have more possibility than the decomposition steps proposed by Peter Politzer.